The effects of CSR performance on analyst forecast bias and forecast dispersion. - Phua, Kenny Jing Wen. (2013)
We examine the relationship between CSR performance measures and analysts’ earnings forecast bias and dispersion. Our empirical findings reveal that current and historical CSR concerns are associated with negative forecast bias while current CSR strengths are related to positive forecast bias. Additionally, we find that forecast dispersion increases with current and historical concerns while an inverse relationship is observed between forecast dispersion and current strengths. The effect of historical strengths is statistically indistinguishable from zero in both forecast bias and dispersion. Separately, only current concerns yield a statistically significant (and positive) association with absolute forecast error. The results are robust to various control factors known to affect forecast characteristics.